The Forces of the Hyksos and Their Representations: Glimpse of Reality or interpretatio Thebarum? - Uroš Matić (Arts)
Not much is known about the forces of the Hyksos, 15th Dynasty rulers of the Second Intermediate Period in Egypt. This was a time when Egypt and Nubia were divided between several competing royal houses and corresponding dynasties, e.g., the 14th and 15th Dynasty in Lower Egypt, 16th and 17th Dynasty in Upper Egypt, as well as the Kushite kingdom in Nubia. Loyalty to any of these polities was not based on ethnic identity. Forces of different ethnicities could pledge loyalty to any of the competitors. Bearing in mind the multi-ethnic population on the territory under the Hyksos rule, this article discusses the reality behind ideologically colored Theban representations of the Hyksos forces as consisting solely of foreigners. Starting from the premise that royal artistic production is deeply entangled with power in ancient Egypt, this article analyzes the ways private and royal inscriptions as well as literary and visual representations were employed to construct the cultural memory of the Second Intermediate Period which privileged the experience of Theban victors and degraded the experience of their rivals.